Measuring Indonesian Students’ Lexical Diversity and Lexical Sophistication - FAILASOFAH FAILASOFAH; HAZIM TAISIR DAYIJ ALKHRISHEH (Universitas Jambi, Indonesia, 2018)
The aim of the present study was to look at a description of Indonesian EFL students’ vocabulary knowledge. The focus was on their lexical diversity (how many different words students used) and lexical sophistication (how many advance words students used) in the English production, which is learnt by them as a foreign language. Their vocabulary knowledge was assessed using the D_tools and P_Lex software for the analysis. These statistical programs describe students’ detail computation results in both number and graph. Ten participants’ word production through a story-telling test was recorded and analyzed to look at their D and Lambda value. Based on the results gathered, it can be concluded that as foreign language learners, lower level of proficiency participants could produce more lexically rich texts than higher level participants and vice versa.